RISKS AND BENEFITS OF SPINAL FUSION SURGERY FOR DEGENERATIVE SPINE DISEASES: SYSTEMATIC REVIEW OF LITERATURE - Pedro Henrique Rodrigues; Italo Nunes Vieira; Wander Arraes Gonçalves; Max Belem Fernandes (Acta Ortopédica Brasileira)
ABSTRACT Degenerative spine diseases are a common cause of low back pain and neurological dysfunction, often associated with aging, and may require surgical interventions when conservative treatment is ineffective. This study aims to evaluate the risks and benefits of minimally invasive spinal fusion surgery (MIS) compared to open surgery (OS) for the treatment of these conditions. Through a systematic review, 83 studies were analyzed, of which 10 were included in the meta-analysis. The methodology followed PRISMA guidelines, with searches in PubMed, Scopus, Web of Science, Medline Ovid, and SciELO databases. The results indicate that MIS offers several advantages over OS, including lower intraoperative blood loss, reduced postoperative pain, shorter hospital stay, and lower incidence of complications, without compromising bone fusion rates. These findings suggest that MIS is an effective and potentially superior alternative to OS, with significant benefits for patient recovery. However, specialized training is required to ensure the safety and efficacy of the procedure. Level of Evidence l; Systematic review.